Pengaruh Pemeriksaan Internal (Audit Intern) Terhadap Efektivitas Pengendalian Internal (Studi Kasus pada PT. Bank Rakyat Indonesia (Persero) Tbk.) - Dena Eka Agustina (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2020)
The Influence of Internal Audit on Internal Control Effectiveness (cases at PT. Bank Rakyat Indonesian (Persero) Tbk. Sukabumi Branch Office). Adviser Sutrisno, M.Ak and Rizal Zaelani, SE., MM. The objective of this study is to determine whether internal audit influenced the internal controls effectiveness at PT. Bank Rakyat Indonesian (Persero) Tbk. Sukabumi Branch Office. The factors tested in this research werw the internal audit as the independent variable and the effectivity of the internal control as the dependent variable. Respondents in this study were the employee and internal audit PT. Bank Rakyat Indonesian (Persero) Tbk. Sukabumi Branch Office. Of the questionnaries distributed, obtained 33 respondent were included in the data processing. Data nalysis using SPSS verson 23. The type of data used are primary data and secondary data. Results of data collected than analized using validity and reliability test, normality test, simple linear regression analysis, hypothesis testing using t test, and coefficient of determination testing. Validity test results showed that all of the questionnaries for the independent variable and dependent variable was reliable. The result of classical assumption of normality test showed that the role of internal audit in supporting the internal control effectiveness is normally distributed. Value t- test 4,050 > t- table 1,695 and value significantly 0,000 < 0.05. The results showed that the internal audit positive significantly influence the internal control effectiveness at PT. Bank Rakyat Indonesian (Persero) Tbk. Sukabumi Branch Office with 34,6% of contribution, as for the remaining 65,4% was influenced by other variables outside the study model.